2017
DOI: 10.1016/j.ypmed.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

A Multiple Streams analysis of the decisions to fund gender-neutral HPV vaccination in Canada

Abstract: In Canada, the human papillomavirus (HPV) vaccine is licensed and recommended for females and males. Although all Canadian jurisdictions fund school-based HPV vaccine programs for girls, only six jurisdictions fund school-based HPV vaccination for boys. The research aimed to analyze the factors that underpin government decisions to fund HPV vaccine for boys using a theoretical policy model, Kingdon's Multiple Streams framework. This approach assesses policy development by examining three concurrent, but indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 100 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…Most cost effectiveness studies are focused on whether vaccinating men is cost effective in decreasing cervix cancer in women. These studies show that vaccinating men is not cost effective, especially when female coverage is moderate-high [8] . Cost effectiveness data is more favorable for vaccination of men when considering all HPV related diseases and when female vaccination rates are below 40% [9] .…”
Section: Introductionmentioning
confidence: 88%
“…Most cost effectiveness studies are focused on whether vaccinating men is cost effective in decreasing cervix cancer in women. These studies show that vaccinating men is not cost effective, especially when female coverage is moderate-high [8] . Cost effectiveness data is more favorable for vaccination of men when considering all HPV related diseases and when female vaccination rates are below 40% [9] .…”
Section: Introductionmentioning
confidence: 88%
“…7,8 As of 2018, all jurisdictions also offer programs for boys in schools; 9 however, the roll out of these programs (since 2013) has been staggered and HPV vaccination rates in Canada remain suboptimal. 3,8,10 Because HPV vaccination targets children, 3 parental acceptance is critical to ensuring uptake. Previous research has indicated common themes associated with uptake, such as the importance of parents believing in the benefits of vaccination and perceiving few barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Since HPV vaccine programmes and policies are constantly evolving, 25 it is timely to evaluate comprehensively variations in programme outcomes that target girls and boys, jurisdictions at a national and local level and HPV vaccination by sociodemographic groups. For this reason, this study will be useful to policymakers in understanding where the HPV vaccination programmes are meeting coverage targets, where disparities in vaccination exist, and which groups or jurisdictions may benefit from interventions designed to increase vaccination.…”
Section: Discussion Study Implicationsmentioning
confidence: 99%
“…26 To date, only a handful of countries have extended their publicly funded, school-based HPV vaccination programmes to boys. 25 27 28 Investigating Canadian parents' HPV vaccine knowledge, attitudes and behaviour: a study protocol for a longitudinal national online survey Gilla K Shapiro, 1,2 Samara Perez, 1,2 Anila Naz, 2 Ovidiu Tatar, 2 Juliet R Guichon, 3 Rhonda Amsel, 1 Gregory D Zimet, 4 Zeev Rosberger 1,7,2,5,6 To cite: Shapiro Open Access Figure 1 Publicly funded school-based HPV vaccine programmes in Canada. This figure identifies the year that publicly funded school-based HPV vaccine programmes were initiated for girls and boys by Canadian jurisdiction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation